Reflections on education for sustainable development and the new UNESCO recommendation on education for peace, human rights and sustainable development - Kohl, Katrin; Sanusi, Zainal Abidin; Hussien, Suhailah (Kulliyyah of Education, International Islamic University Malaysia., 2025)
Education for Sustainable Development (ESD) has been a pivotal, yet evolving concept in the global discourse on sustainability since its introduction in Agenda 21 (1992). This article critically examines the recent UNESCO Recommendation on Education for Peace, Human Rights and Sustainable Development (2023) in light of ESD’s disputed definition(s), functions, and intended outcomes including perspectives on philosophical underpinnings. The analysis applies Critical Social Theory and uses critical discourse analysis. The findings show that despite the UNESCO Recommendation’s claim of creating consensus on definitions of concepts including ESD, it perpetuates existing inconsistencies and vagueness, thereby hindering implementation and fulfilment of the enabling role of ESD. The study demonstrates that the UNESCO Recommendation includes references to humanistic thought without acknowledging or addressing potential limitations in relation to diverse worldviews. Following an extensive literature review published in 2024 (Kohl et al., 2024), this article is a second insight into doctoral research underway at the International Islamic University Malaysia (IIUM). The research analyses the ESD-related UN/UNESCO discourse between 1992 and 2023, examining ESD’s understanding and references to humanistic thought. Moving forward, the authors call for pluralistic perspectives on ESD that embrace a shared basis and philosophical grounding to support context-sensitive implementation.